2019
DOI: 10.3389/fpls.2019.00204
|View full text |Cite
|
Sign up to set email alerts
|

Remote Estimation of Rice Yield With Unmanned Aerial Vehicle (UAV) Data and Spectral Mixture Analysis

Abstract: The accurate assessment of rice yield is crucially important for China’s food security and sustainable development. Remote sensing (RS), as an emerging technology, is expected to be useful for rice yield estimation especially at regional scales. With the development of unmanned aerial vehicles (UAVs), a novel approach for RS has been provided, and it is possible to acquire high spatio-temporal resolution imagery on a regional scale. Previous reports have shown that the predictive ability of vegetation index (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 50 publications
3
70
0
1
Order By: Relevance
“…The result could be ascribed to the fact that the data were segmented into too many groups (number of groups = 36) when using CSP as random effects. Therefore, the number of points per group was very low (i.e., [12][13][14][15][16][17][18][19][20][21][22][23][24] and the modelling performance within the groups suffered from randomness and strong uncertainty. Even though the LME model (using CSP) achieved good performance over all data, this approach would lose statistical significance and simply yield the mean for the group.…”
Section: Comparison Of Lme Models With Different Random Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result could be ascribed to the fact that the data were segmented into too many groups (number of groups = 36) when using CSP as random effects. Therefore, the number of points per group was very low (i.e., [12][13][14][15][16][17][18][19][20][21][22][23][24] and the modelling performance within the groups suffered from randomness and strong uncertainty. Even though the LME model (using CSP) achieved good performance over all data, this approach would lose statistical significance and simply yield the mean for the group.…”
Section: Comparison Of Lme Models With Different Random Effectsmentioning
confidence: 99%
“…For example, Devia et al used seven vegetation indices, combined with multivariable regressions to monitor agronomy parameters at different rice growth stages [15]. Duan et al integrated UAV-based vegetation indices (VIs) and abundance information obtained from spectral mixture analysis to improve the prediction accuracy of rice yield at the heading stage [16]. In addition, most UAV-based studies used multi-rotor UAVs due to their high stability, superior image quality and good controllability.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput eld phenomics for aerial imaging of cassava UAV offers very attractive alternatives such as, convenient operation, high spatial and temporal resolutions with reasonable spatial coverage [57][58][59], makes it possible to document the within-microplot variability in phenotyping eld experiments [60,61]. UAV, a current and an invaluable tool for crop monitoring at large scale (e.g., [27,59,[62][63][64][65], has been proved to be useful for estimating canopy height and biomass in crops including rice [65], wheat [66] maize [30], sorghum [67] and peas [17]. However, in cassava, the UAV based high-throughput phenotyping methods need to be standardized for feasibility and accuracy in estimating various phenotyping parameters such as, biotic and abiotic stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the single-stage results, in the OCW-based models, the accuracy of the rLAI model is higher than that of the rVI model. Because the appearance of saturation phenomenon in yield estimation using spectral index will limit the accuracy of models to some extent [25]. The LAI data is the three-dimensional (3D) information of the crop, and the limitations will be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al [24] found that NDVI is of great help to the prediction of rapeseed yield using unmanned aerial vehicle (UAV) imagery. Moreover, VI also contributes signi cantly to yield estimation for crops such as rice [25][26], maize [27][28] and wheat [29][30]. The simulation results of crop characteristic parameters can be obtained by constructing the linear or nonlinear empirical relationship [31] or by machine learning methods [32] like support vector machine (SVM), random forest (RF), partial least squares (PLS) and arti cial neural network (ANN) between VIs and these parameters.…”
Section: Introductionmentioning
confidence: 99%